DESIGN AND OPTIMIZATION OF MODULAR PRODUCTION SYSTEM PICK & PLACE STATION - Siva, Farrell; Purna Irawan, Agustinus; Halim, Agus; Widya Utama, Didi (POROS, 2023)
In the industrial era 4.0 where the development of sophisticated technology, the development of technology has been increasingly rapid. The industry itself began to use this sophisticated technology with the aim of seeking maximum profit with minimum capital, so for that reason the industry began to switch to "Industrial Automation". With the aim of understanding the complicated production process, MPS (Modular Production System) is made with the aim of facilitating understanding of the related production process where the MPS to be studied is Pick & Place Station. The method to be used is an experimental method where what will be studied is the effect of flowcontrol openings on cycle time, the effect of flowcontrol openings on flowsensor data, vacuum lift force, vacuum force using the venturi principle. Where the greater the flowcontrol opening, the faster the cycle time will be with the risk of cylinder damage where the first entry group produces a slower cycle time than the cycle time produced by the second entry group. The flowcontrol opening itself also affects the data in the flowsensor where the data for average mass flowrate, average flow velocity, average volumetric flowrate, average temperature, and average pressure shown by data entry 1 is smaller than data entry 2. The vacuum lift force for entry 1 and entry 2 has the same value or there is a very small change for both the distribution station and the pick & place station. For vacuum force with the venturi principle, data entry group 1 produces a smaller force than data entry group 2.